Rethinking m(6)A Readers, Writers, and Erasers - Meyer, Kate D. (Annu Rev Cell Dev Biol, 2017)
In recent years, m(6)A has emerged as an abundant and dynamically regulated modification throughout the transcriptome. Recent technological advances have enabled the transcriptome-wide identification of m(6)A residues, which in turn has provided important insights into the biology and regulation of this pervasive regulatory mark. Also central to our current understanding of m(6)A are the discovery and characterization of m(6)A readers, writers, and erasers. Over the last few years, studies into the function of these proteins have led to important discoveries about the regulation and function of m(6)A. However, during this time our understanding of these proteins has also evolved considerably, sometimes leading to the reversal of early conceptions regarding the reading, writing and erasing of m(6)A. In this review, we summarize recent advances in m(6)A research, and we highlight how these new findings have reshaped our understanding of how m(6)A is regulated in the transcriptome.